Sporadic pancreatic neuroendocrine neoplasms: A retrospective clinicopathological and outcome analysis from a Latvian study group - Ptasnuka, Margarita; Truskovs, Arturs; Ozolins, Arturs; Narbuts, Zenons; Sperga, Maris; Plaudis, Haralds (Frontiers in Surgery, 2023)
Patients with confirmed PNEN at Riga East Clinical University Hospital and Pauls Stradins Clinical University Hospital, between 2008 and 2020, were retrospectively analyzed. Data were collected and included in EUROCRINE, an open-label international endocrine surgical registry. Results: In total, 105 patients were included. The median age at diagnosis was 64 years (IQR 53.0–70.0) for males and 61 years (IQR 52.5–69.0) for females. In 77.1% of patients, tumors were hormonally nonfunctional. Among those with functioning PNEN, 10.5% of patients presented with hypoglycemia and were diagnosed with insulinoma, 6.7% of patients presented with symptoms related to carcinoid syndrome; 30.5% of patients showed distant metastases at the time of diagnosis, and surgery was performed in 67.6% of patients. Notably, for five patients with nonfunctional PNEN <2 cm, a “watch and wait” approach was used; none of the patients developed metastatic disease. The median length of hospital stay was 8 days (IQR 5–13). Major postoperative complications were found in 7.0% of patients, and reoperation was conducted for 4.2% of patients, due to postpancreatectomy bleeding (2/71) and abdominal collection (1/71). The median follow-up period was 34 months (IQR 15.0–68.8). The OS at the last follow-up was 75.2% (79/105). The observed 1-, 5- and 10-year survival rates were 87.0, 71.2 and 58.0, respectively. Seven of the surgically treated patients had tumor recurrence. The median time of recurrence was 39 months (IQR 19.0–95.0). A univariable Cox proportional hazard analysis provided evidence that a nonfunctional tumor, a larger tumor size, the presence of distant metastases, a higher tumor grade, and the tumor stage were strong, negative predictors of OS. Conclusion: Our study represents the general trends of clinicopathological features and treatment of PNEN in Latvia. For PNEN patients, tumor functionality, size, distant metastases, grade, and stage may be useful to predict OS and must be confirmed in further studies. Furthermore, a “surveillance” strategy might be safe for selected patients with small asymptomatic PNEN.